Implementasi Pendekatan Additive Ratio Assessment Pada Sistem Pendukung Keputusan Pemilihan Board Microcontroler - Rini Nuraini (PDSI, 2023)
Technology is currently developing into automation in the form of intelligent systems and the Internet of Things. These technologies will be related to components, one of which is a microcontroller. Today, there are more and more choices of microcontrollers with various specifications. Due to the large variety of microcontroller board products available on the market, one must understand one by one the specifications of the device to be purchased. It takes a long time for someone to make a choice. The research aims to develop a Decision Support System (DSS) using the Additive Ratio Assessment (ARAS) to assist in choosing a microcontroller board, so that it can assist in determining the best alternative appropriately and according to needs. The ARAS approach can select the best alternative based on the utility level of each alternative in determining the ranking of the best alternative or alternative. Based on the results of the case study conducted, the highest utility value was NodeMCU ESP8266 with a value of 0.8873, followed by FireBeetle ESP32 with a value of 0.8357, Arduino Uno R3 with a value of 0.5815 and Quark D2000 with a value of 0.5298. The calculation results obtained by the system by calculating manually show the acquisition of the same value. In addition, based on the results of black box testing, it shows that all the features tested have worked well